2014
DOI: 10.1093/sysbio/syu055
|View full text |Cite
|
Sign up to set email alerts
|

Coalescent versus Concatenation Methods and the Placement of Amborella as Sister to Water Lilies

Abstract: The molecular era has fundamentally reshaped our knowledge of the evolution and diversification of angiosperms. One outstanding question is the phylogenetic placement of Amborella trichopoda Baill., commonly thought to represent the first lineage of extant angiosperms. Here, we leverage publicly available data and provide a broad coalescent-based species tree estimation of 45 seed plants. By incorporating 310 nuclear genes, our coalescent analyses strongly support a clade containing Amborella plus water lilies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
355
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(385 citation statements)
references
References 106 publications
26
355
4
Order By: Relevance
“…alone (Qiu & al., 1999;, followed by Nymphaeales, or of Amborella plus Nymphaeales (Barkman & al., 2000;Qiu & al., 2010). Both scenarios are still discussed today based on extended sampling and techniques (Drew & al., 2014;Xi & al., 2014;Goremykin & al., 2015). The next clade in the grade, which is the sister group of mesangiosperms in virtually all analyses, is Austrobaileyales.…”
Section: Introductionmentioning
confidence: 99%
“…alone (Qiu & al., 1999;, followed by Nymphaeales, or of Amborella plus Nymphaeales (Barkman & al., 2000;Qiu & al., 2010). Both scenarios are still discussed today based on extended sampling and techniques (Drew & al., 2014;Xi & al., 2014;Goremykin & al., 2015). The next clade in the grade, which is the sister group of mesangiosperms in virtually all analyses, is Austrobaileyales.…”
Section: Introductionmentioning
confidence: 99%
“…Successfully identifying different sources of discord Lould alloL us partition a large dataset into homogenous subsets that can be adequately modeled by existing methods (e.g., Chen et al, 2015;Xi et al, 2014). In this sense, CLASSIPHY analysis frameLork Lould be complementary to various data filtering tools that have been proposed to address the negative impact of data heterogeneity on phylogenomic estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Or reflect biases in data processing steps and tree reconstruction methods (e.g., Dell'Ampio et al, 2014;Fernández-Mazuecos et al, 2017)? Or are driven by strong signals in small number of genes or sites (Lhich could be outliers; e.g., Shen et al, 2017;Xi et al, 2014)? Many data filtering strategies Lere proposed based on "interrogating" large empirical datasets, from rate of evolution to gene functional categories (e.g., Betancur et al, 2014;Doyle et al, 2015;Klopfstein et al, 2017;Romiguier et al, 2013;Salichos and Rokas, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more critical evaluation of DNA characters has reduced confidence in the basal placement of Amborella (9) and has demonstrated that the incorporation of highly Fossils such as those reported for Monteschia can only help to unravel the evolutionary and ecological events that accompanied the rise of flowering plants to global prominence. saturated sites can alter the position of Amborella and Ceratophyllum in phylogenetic analyses (10,11). The following inconsistencies are particularly noteworthy.…”
mentioning
confidence: 99%